Impact of privatization on the Latin American debt problem. - RAMAMURTI, Ravi (1992)
Discusses the extent to which state-owned enterprises were responsible for creating the Latin American debt problem, and, the extent to which the present privatization of those enterprises may help to resolve that problem.